Assistive technologies for children with cognitive and/or motor disabilities: interviews as a means to diagnose the training needs of informal caregivers. (3rd April 2021) - Carmo Rodrigues Almeida, Ivone; Ribeiro, Jaime; Moreira, António
Abstract: Purpose: The present study seeks to survey information and training needs of informal caregivers related to the use of assistive technologies at home, so as to, in the near future, try to meet them. Therefore, the full aim of this study is to contribute to reducing technology abandonment and to enhancing its use in the family setting by children with cognitive and/or motor limitations. Materials and methods: Content analysis of a set of ten interviews with informal caregivers of children and youngsters with cognitive and/or motor disabilities. Results: Assistive technologies open a wide range of opportunities, mostly to students whose learning skills diverge from standard development. They promote communication, independence as well as inclusion of children with cognitive and/or motor disabilities. Despite the human and material resources available, the implementation of assistive technologies in many family settings is still a struggling task. The results reveal a perspective on (i) the interaction between those caregivers and their children, (ii) children's skills in using assistive technology, (iii) caregivers' digital literacy and (iv) their training needs. Conclusions: The present paper highlights the fact that carrying out interviews with informal caregivers leads to obtaining significant data for a diagnosis of the use of assistive technologies in the family setting and to assess the needs of informal caregivers. From this study, the need to provide caregivers with further training on assistive technologies emerges as preponderant, and to improve caregivers' skills in the search for and access to practical information. Implication for Rehabilitation: Cognitive and/or motor disabilities impact on communication, independence and also on the full inclusion of children, especially when efforts developed at school do not have any follow up at home. Endowing informal caregivers with the knowledge and skills to use assistive devices with their children is a step forward to their full development. Interviews conducted with informal caregivers are a means to gaining insights into understanding the reasons behind assistive technology abandonment at home.